DOP26 Burden of perianal disease and perianal surgery in Crohn's disease over different therapeutic eras – a population-based study from western Hungary between 1977–2020, data from the Veszprem county cohort. (30th January 2023) - Gonczi, L; Lakatos, L; Golovics, P A; Pandur, T; David, G; Erdelyi, Z; Szita, I; Lakatos, P L
Abstract: Background: Few population-based studies have investigated rates and management of perianal disease and long-term perianal surgery rates in Crohn's disease (CD). The present study is a continuation of the Veszprem IBD population based cohort with a follow-up osince 1977. Our aim was to analyze the long-term rates of perianal surgical procedures over different therapeutic eras in a prospective population-based database from Veszprem Province, including incident CD patients. Methods: Patient inclusion was between January 1, 1977 and December 31, 2018; follow-up ended December 31, 2020. Both in-hospital and outpatient records were collected. Perianal surgical procedure was defined as any perianal surgical procedure including fistulotomy, abscess drainage or seton placement. Surgery rates were examined in three different eras based on time of diagnosis: cohort-A, 1977-1995; cohort-B, 1996-2008; and cohort-C, 2009-2018. Results: Data of 946 incident CD patients were analyzed (male/female: 496/450; median age at diagnosis: 28 years(y) [IQR: 22-40]). Median follow-up time for the entire cohort was 15 years (IQR: 9-21). Table 1. Perianal disease at diagnosis was present in 17.4% (n=165) of the total cohort, and in 24.7%/ 18.5%/ 13.2% in cohorts A/B/C, respectively. By the end of follow-up, an additional 9.3% (n=88) of the total cohort developed perianal disease. Cumulative immunosuppressive and biologic therapy exposure increased by time in cohorts A/B/C ( Table 2 and Figure 1 ), and biologic use was higher in patients with perianal disease compared to the overall population. Figure 2. The overall rate of perianal surgical procedures was 44.7% (113/253) in patients with perianal disease during the total follow-up. The cumulative probability of perianal surgical procedure in patients with perianal disease was 28.3±2.9% after 10 years, 41.0±3.5% after 20 years, and 64.1±5.1% after 30 years. No statistically significant differences have been observed in the cumulative probability of perianal intervention between cohorts A/B/C: 24.2±5.4%/ 19.9±3.5%/ 29.4±5.8% after 5 years; 33.9±6.0%/ 23.6±3.8%/ 31.7±6.1% after 10 years; [LogRank=0.594]. Figure 3. C ox-regression multivariate analysis showed that stenosing or penetrating disease (B2/B3) behavior (HR 1.81; 95%CI 1.19-2.75; p=0.005) was independent predictor of perianal surgical procedure. Table 3. Conclusion: The burden of perianal disease and perianal surgical interventions was high in this cohort. Patients with perianal CD had higher exposure to biologicals. No difference was observed in perianal surgical intervention rates despite the increasing use of immunosuppressives and biologicals over time, however these procedures may partly represent a medical decision and the complex management of perianal disease.